Why we should talk about option generation in decision-making research - Kalis, Annemarie; Kaiser, Stefan; Mojzisch, Andreas (Frontiers in Psychology, 2013)
Most empirical studies on decision-making start from a set of given options for action. However, in everyday life there is usually no one asking you to choose between A, B and C. Recently, the question how people come up with options has been receiving growing attention. However, so far there has been neither a systematic attempt to define the construct of ‘option’ nor an attempt to show why decision-making research really needs this construct.This paper aims to fill that void by developing definitions of ‘option’ and ‘option generation’ that can be used as a basis for decision-making research in a wide variety of decision-making settings, while clarifying how these notions relate to familiar psychological constructs. We conclude our analysis by arguing that there are indeed reasons to believe that option generation is an important and distinct aspect of human decision-making.